Evaluation of deficiencies in current discharge summaries for dialysis patients in Canada - Harel, Ziv (Dove Medical Press, 2012)
BACKGROUND: Deficits in the transfer of information between inpatient and outpatient physicians are common and pose a patient safety risk. This is particularly the case for vulnerable populations such as patients with end-stage renal disease requiring dialysis. These patients have unique and complex health care needs that may not be effectively communicated on standard discharge summaries, which may result in potential medical errors and adverse events. OBJECTIVE: To evaluate Canadian dialysis center directors’ perceptions of deficiencies in the content and quality of hospital discharge summaries for dialysis patients. METHODS: A web-based, cross-sectional survey of Canadian dialysis center directors was performed between September and November 2010. The survey consisted of three parts. The first part was designed to assess dialysis center directors’ attitudes on the quality of discharge summaries they receive. The second part was designed to elicit respondents’ preferences for discharge summary content, and the third part consisted of questions regarding demographic and practice information. RESULTS: Of 79 dialysis center directors, 21 (27%) completed the survey. Sixty-two percent felt that current discharge summaries inadequately communicate dialysis-specific information. Receipt of antibiotics for line sepsis or peritonitis, modifications to vascular access, and changes in target weight/dialysis prescription were rated as essential dialysis-specific information to include in discharge summaries by respondents. CONCLUSION: Over three quarters of dialysis center directors find the current practice of transferring discharge information for hospitalized dialysis patients grossly inadequate. The inclusion of dialysis-specific information may improve the quality of discharge summaries for dialysis patients.